2018
DOI: 10.1007/s12529-018-9718-z
|View full text |Cite
|
Sign up to set email alerts
|

Fruit and Vegetable Intake: the Interplay of Planning, Social Support, and Sex

Abstract: Even though intention and planning are predictors of dietary change, they operate differently under specific conditions (level of social support), for specific subgroups (men vs. women), and for different target behaviors (fruit vs. vegetable intake). These results suggest to further examine the mechanisms by which intentions are translated into behavior via planning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 49 publications
1
14
0
3
Order By: Relevance
“…Studies on cognitive behavioral therapy (CBT) and habit management have been included in the “life purpose” pillar. As can be seen in Figure 2, the five studies focused on physical activity [27,32,34,36,37] represent a third of the total, and the five focused on life purpose studies [28,30,35,39,40] represent another third. Four of the studies related to the “life purpose” pillar [30,32,41,42] (80% of the “life purpose” pillar related studies and 26.66% of the total of studies) focus on habit management and CBT.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies on cognitive behavioral therapy (CBT) and habit management have been included in the “life purpose” pillar. As can be seen in Figure 2, the five studies focused on physical activity [27,32,34,36,37] represent a third of the total, and the five focused on life purpose studies [28,30,35,39,40] represent another third. Four of the studies related to the “life purpose” pillar [30,32,41,42] (80% of the “life purpose” pillar related studies and 26.66% of the total of studies) focus on habit management and CBT.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 3 shows the classification of studies according to how they monitor subjects. Eight of the studies identified (53.33%) [30,31,32,33,35,37,40,41] employed light monitoring, based on questionnaires and tests to get data and parameters from users. Three of the studies [29,36,39] (20%) employed heavy monitoring with controlled spaces or specific devices.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides being positive influenced by individual engagement and active effort, the effective health promotion, lifestyle modifications, and preventive interventions are leveraged by a supportive social environment for patients and users. Specifically, emotional and instrumental social support from partners, relatives, and friends may facilitate self-care, behavioral change, and adherence to treatment in healthy people and patients with chronic diseases (Finlay et al 2018;Holt-Lunstad 2018;Lange et al 2018;Tregarthen et al 2015;Uchino et al 2018). By recognizing the pivotal role of social influence and support for the effectiveness of each preventive effort, several traditional and eHealth interventions have included specific features aimed at leveraging social influence to promote self-management skills, screening behaviors, lifestyle modifications, and treatment adherence.…”
Section: Strategies Of Ehealth Preventionmentioning
confidence: 99%
“…Furthermore, they stress the idea of food as a social surrogate, demonstrating how (comfort) food choice is often associated with social isolation. As Connor and Armitage (2002) claimed, social psychologists contribute to food research by addressing topics as factors in food choice (McFerran et al, 2009), dietary change (Lange et al, 2018), weight control and well-being (Utter et al, 2018), snacking (Schüz et al, 2018), and food and self-presentation (Herman et al, 2003). In this context, the most thoroughly explored topic is what social psychology defines as the social facilitation of eating (e.g., Herman, 2015Herman, , 2017.…”
Section: Food As a Social Phenomenonmentioning
confidence: 99%